Rhodium(III)‐Catalyzed ortho CH Heteroarylation of (Hetero)aromatic Carboxylic Acids: A Rapid and Concise Access to π‐Conjugated Poly‐heterocycles1. (27th April 2015) - Qin, Xurong; Li, Xiaoyu; Huang, Quan; Liu, Hu; Wu, Di; Guo, Qiang; Lan, Jingbo; Wang, Ruilin; You, Jingsong
Abstract RhIII‐catalyzed oxidative CH/CH cross‐coupling between (hetero)aromatic carboxylic acids and various heteroarenes has been accomplished to construct highly functionalized ortho‐carboxy‐substituted bi(hetero)aryls. The use of a carboxy group as the directing group obviates tedious steps for installation and removal of extra directing groups, and enables a facile one‐step synthesis of ortho‐carboxy bi(hetero)aryls. The method provides opportunities for rapid assembly of a library of important fluorene and coumarin‐type poly‐heterocycles through intramolecular electrophilic substitution or oxidative lactonization. As illustrative examples, the strategy developed herein greatly streamlines accesses to a variety of appealing polyheterocycles such as DTPO (5H‐dithieno[3, 2‐b:2′, 3′‐d]pyran‐5‐one), CPDTO (cyclopentadithiophen‐4‐one), and indenothiophenes.